Interdiffusion of Al and Ga in AlN/AlGaN superlattices grown by ammonia-assisted molecular beam epitaxy. (February 2021) - Nemoz, M.; Semond, F.; Rennesson, S.; Leroux, M.; Bouchoule, S.; Patriarche, G.; Zuniga-Perez, J.
Abstract: Diffusion at the AlN/Al0.3 Ga0.7 N interface was investigated by X-ray diffraction, high-angle annular dark field scanning transmission electron microscopy and energy-dispersive X-ray spectroscopy. AlN/Al0.3 Ga0.7 N superlattices (SLs) have been grown at 800 °C on (111) silicon substrates by ammonia-assisted molecular beam epitaxy. Annealings on a 5-pair SL, carried out at the growth temperature in an ammonia-based atmosphere from 1h to 115h, show the occurrence of a diffusion process illustrated by the increase of the interface layer thickness. The cation interdiffusion is found to be weakly concentration-dependent while it seems to be more strain-dependent. The mean diffusion coefficient value determined in this study at the AlN/Al0.3 Ga0.7 N interface is about 6⨯10 −18 cm 2 /s at the growth temperature. The effect of the unintentional annealing of buried layers during long growth runs is exemplified on a 45-pair SL. The measurement of the actual composition profile along the growth direction shows the formation of an unintentional AlGaN graded layer of intermediate composition at each interface. The thickness of each of these interfacial layers is found to decrease along the SL growth direction, pointing towards the influence of the overall time spent at growth temperature as a determining parameter. Highlights: Interdiffusion of Al and Ga occurs at 800 °C in AlN/Al0.3 Ga0.7 N superlattices. The mean cation diffusion coefficient value at 800 °C in Alx Ga1-x N is 6*10 −18 cm 2 /s. Cation diffusion is weakly concentration-dependent but strongly strain-dependent. Long growth runs enhance interdiffusion of buried layers.